Kondisi dan Keanekaragaman Jenis Lamun di Perairan Pulau Serangan, Provinsi Bali - Luh Gede Manik Radzena Martha; Pande Gde Sasmita Julyantoro; Alfi Hermawati Waskita Sari (Fakultas Kelautan dan Perikanan Universitas Udayana, 2019)
Serangan Island is one of the tourism destinations in Bali which is administratively belong to the municipality of Denpasar. Tourism development near with the segrass habitat cause the segrass ecosystem being degraded in the waters of Serangan Island. This study was aimed to determine the diversity and conditions of seagrass species which were observed from the density and percentage of seagrass coverage and to examine the effect of water quality on the percentage of seagrass coverage. This research was conducted from February to March 2017 on Serangan Island using quantitative descriptive method. Sampling was conducted at three stations by taking data and samples of seagrass, measuring water quality (temperature, salinity, pH, turbidity, substrate observation) and analyze of nitrates and phosphates content. Seven types of seagrass species were found i.e. Enhalus acoroides, Thalassia hemprichii, Cymodocea rotundata, Halophila ovalis, Halodule pinifolia, Syringodium isoetifolium, and Thalassodendron ciliatum. The study showed that the diversity index value was in the medium category. The density of seagrass was classified as very tight (condition scale of 5). The highest density was found on Cymodocea rotundata spesies at station I about 777 ind/m2. The highest percentage of seagrass coverage (79,55%) was found in station I which classified as good condition, while station II and station III were classified as damaged condition with value 13.65% and 20,79% respectively. Finally, the water quality parameters have relatively low effect to seagrass coverage percentage.